LOW-LINEAR ENERGY TRANSFER RADIOLYSIS OF SUPERCRITICAL WATER AT 400 °C: DENSITY DEPENDENCE OF THE G(•OH) - Sofia Loren Butarbutar; Geni Rina Sunaryo; J. Meesungnoen; J.P. Jay-Gerin (SIGMA EPSILON - Buletin Ilmiah Teknologi Keselamatan Reaktor Nuklir, 2016)
Monte Carlo simulations were used to predict the yield of primary specie •OH denoted as g(•OH) that is formed from the radiolysis of pure, deaerat- ed supercritical water (SCW) (H2O) at 400 °C in the range of water density between ~0.15 and 0.6 g/ cm3. It is known that •OH, is one of the oxidizing species that significantly can increase the possibil- ity of various corrosion and material degradation as well. The thorough radiolysis processes in SCW- cooled reactor is not established currently, and it is believed to be a challenge in developing chemis- try control strategies for future Supercritical Water Reactor (SCWR). Since SCWR technology is now still under the conceptual design, hence there is only limited information published on the yields of radiolysis under these conditions. In this work, g(•OH) was calculated at spur lifetime (τs/ minimum time needed before the species within spur distributed homogeneously into the bulk solu- tion), 10-7 and 10-6 sec after the ionization event at all densities. From this work, it is shown that the data measured by other researcher at lower density (<0.35 g/cm3) is taken at longer time, while at higher density (>0.35 g/cm3) is taken about near the spur lifetime. Finally, more experimental data are highly required in order to examine more thoroughly modeling calculation.